The Community Law Compliance with Marriage Age Limitation Provisions - Wahab, Abdul; Khisni, Akhmad (Universitas Islam Sultan Agung, 2021)
The objectives of this research are to find out and analyze the community's legal compliance with Act No. 16 of 2019 concerning the Provisions on the Marriage Age Limit and the inhibiting factors for the implementation of Act No. 16 of 2019 concerning the Provisions on the Marriage Age Limit as well as efforts to overcome obstacles to the implementation of Act. This study uses a sociological juridical approach, with descriptive research specifications. The results of this study are Community Legal Compliance with Act No. 16 of 2019 concerning Provisions on Marriage Age Limits, where it is known that public legal awareness of underage marriage is relatively low, where some of the people who already know these rules still register their children's marriages. Inhibiting factors include: First, there are still people who do not know the contents of the policy. Second, there are still people who do not know the benefits. The third is the lack of success of the goal of the law in question is to reduce the rate of marriage at a young age. Efforts to overcome for the prospective bride and groom who have not reached the age of 19 years, their parents/guardians are requested to apply for a Marriage Dispensation to the Religious Court in the area where they live.